Sovereignties - Prokhovnik, R. author. aut Link
VIII, 264 p.
Keywords: Raia Prokhovnik develops a strong argument for sovereignty as a robust concept with many conceptualizations, and capable of further fruitful reconceptualization. The book explores contemporary theoretical developments and current political issues around sovereignty that have crucial practical and institutional implications.